Validasi Metode MPM untuk Penentuan Kandungan Antioksidan dalam Sampel Herbal serta Perbandingannya dengan Metode PM, FRAP dan DPPH - Yefrida Yefrida; Hamzar Suyani; Hermansyah Aziz; Mai Efdi (Jurnal Riset Kimia, 2020)
The Modified Phenanthroline Method (MPM) has been validated for determination of antioxidant content in herb samples. Validation was done using Relative Standard Deviation (RSD) and percentage of recovery. The RSD and percentage of recovery for herb samples are 3.13% and 98.6%, respectively. Based on these values, MPM method is valid for determining antioxidant content in herb samples. T test shows no significant differences of antioxidant content using any of these methods, MPM, PM, FRAP or DPPH, at a 95% confidence level. MPM method shows a very strong correlation with PM and FRAP method.Â  While with DPPH and TPC shows is strong.